Law Enforcement Of Higgs Domino Online Gambling Crimes - Primakova, Giovanni; Achmad , Deni; Monica , Dona Raisa; Raharjo , Eko (Utami Publisher, 2025)
Online gambling has grown rapidly with various types and forms that are always changing. Gambling has developed since ancient times which makes this game always in demand, online gambling is often misinterpreted as just entertainment but a place to find sources of daily income, such as online gambling Higgs Domino, where gambling is a game that can be downloaded on the playstore, the game consists of several types of games such as Domino, Poker, Ludo, and Slot Games which are the same as jackpot machines, where for each game, players must have chips to bet on. based on legal regulations in Indonesia and knowing the negative impacts of online gambling Higgs Domino. Using a legislative approach, this study employs a normative legal method that draws from government documents, legal journals, and primary and secondary legal materials. According to the study's findings, Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions regulates online gaming.